Instrumentation for fluid-particle flow - Soo, S. L. 1922- (Particle technology series., 1999)
A focus on methods of measurement and options for engineers and scientists performing research and evaluation of particle-fluid flow systems. Improved instrumentation for measurement in this field is an essential element in the progress of research and engineering of multi-phase flow systems. Some of the most original and productive research specialists in the field of particle-fluid flow systems are assembled in this book, which is an important and current reference volume.